Beyond the Rash: Simultaneous Bilateral Facial Nerve Palsy Following Childhood Varicella Infection - Mohamed Sheikh Hassan; Abdiwahid Ahmed Ibrahim; Said Abdi Mohamed; Nor Osman Sidow; Said Abdirahman Ahmed; Nur Adam Mohamed; Mohamed Mukhtar Mohamed; Saadaq Adan Hussein (Clinical Case Reports, 2026)
ABSTRACT Bilateral facial nerve palsy is a rare neurological condition in children and is infrequently associated with primary Varicella (chickenpox) infection. We report the case of a 10‐year‐old previously healthy girl who developed simultaneous bilateral lower motor neuron facial weakness 3 weeks after a self‐limiting varicella infection. The patient presented with acute onset inability to close both eyes, difficulty smiling, drooling of saliva, and impaired oral competence. At presentation, the characteristic vesicular rash had completely resolved. Neurological examination demonstrated bilateral lower motor neuron facial nerve palsy with loss of forehead creases, lagophthalmos, flattening of the nasolabial folds, inability to puff the cheeks, and bilateral Bell's phenomenon, without additional neurological deficits. Laboratory investigations and brain magnetic resonance imaging (MRI) were unremarkable. Based on the temporal relationship with recent varicella infection and exclusion of alternative etiologies, a diagnosis of bilateral facial nerve palsy secondary to varicella‐zoster virus infection was established. The patient was treated with intravenous aciclovir, corticosteroids, supportive eye care, and facial physiotherapy. Follow‐up after 6 weeks demonstrated marked clinical improvement, including restoration of facial symmetry, improved eye closure, recovery of smiling ability, and resolution of drooling. This case highlights a rare neurological complication of primary varicella infection and emphasizes the importance of early recognition and multidisciplinary management to achieve favorable neurological outcomes.